Association of Seawater Nanoparticle Size Distribution With Diversity of Marine Plankton - Jiang, Shuangcheng; Lin, Peimei; Cai, Yihua; Chen, Ding; Pan, Zhong; Lin, Hui; Wang, Fuli; Lin, Qi (Frontiers in Water, 2021)
Upon the tangential ultrafiltration and asymmetric flow field analysis, seawater nanoparticle size distribution and the associations with total number of bacteria and plankton diversity were evaluated. 79% of nanoparticles in the Jiulong River Estuary were from 1 to 6 nm (C1). C2 (6-20 nm) were correlated with dissolved organic carbon, while C2 and C3 (>20 nm) were associated with dissolved inorganic nitrogen, suggesting that C2 and C3 were impacted by biogenic elements. The total number of bacteria was correlated with C1 and C3. The correlations of Shannon’s diversity index (H') and C3, richness (d), and C1 suggested the link of particle size with phytoplankton biodiversity. Significant correlations of H' of zooplankton and C3, and Pielou’s evenness index (J) and C3, suggested C3 as a primary digestion product of zooplankton. Negative correlations of nano-organic carbon (NOC) with d and J suggested NOC as a carbon source for zooplankton. Biodiversity was associated with seawater nanoparticle size distribution. The biological activities regulated the nanoparticle size distribution, which impacted the estuarine nutrient cycling, in turn affecting the stability and balance of biodiversity. The correlation analysis of size distribution of seawater nanoparticles and plankton diversity index provided a potential tool for evaluating ecological effects.